Incidences of pelvic limb fractures in dogs: A survey of 478 cases - Shiju Simon; M.; R. Ganesh; S. Ayyappan; G. D. Rao; R. Suresh Kumar; V. R. Kundave and B. C. Das (Veterinary World, 2010)
[Vet. World 2010; 3(3.000): 120-121]